Implementation Of Library Materials For Enhancing Library Collections - Amin, Afriadi; Saragih, Agustina; Tsabitah, Alya; Ridayana, Rizki (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2024)
The library is an incentive that provides and provides a source of information and science to mankind. In fact, a library is a room, part of a building, or the building itself, used to store books and other publications that are generally stored according to the order of data to be used. (Basuki, 1991). In order to ensure high-quality information, the university library should be considered as part of the process of acquiring library material for the fulfilment of the information required by libraries and the development of a reliable collection of information sources. The development of this collection is carried out with the involvement of library staff, executives, researchers, as well as users or librarians. As for the development of this collection, it is the acquisition of library material or acquisition.  The method presented in this article uses library research, i.e. the method of gathering data through understanding and studying the theories of various documents related to research. Library research in research has four stages, namely preparing the necessary documents, preparing work maps, setting time, and reading or recording research materials. This data collection uses a way to find sources and build from a variety of sources, such as books, journals, and previous research. Library materials derived from various references are critically analyzed and need to be further examined to support suggestions and ideas.The quality of a library depends on its collection, and the collection depends upon the selection process. It shows that the choice is very important for the library. If the selection is not properly considered, the library collection may not be able to meet the needs of its users or provide them with satisfaction. This will worsen librarians expectations of libraries. Users may not be allowed to use the library because they feel that they do not get the information they need. Therefore, librarians must be able to carefully and wisely select and select the materials to be included in the library collection.